Electrophysiological investigation. (June 2022) - Sullivan, Andrew; Schilling, Richard; Gall, Nicholas
Abstract: Cardiac electrophysiology is the subspecialty of cardiology dealing with heart rhythm disorders, particularly the investigation and management of bradyarrhythmia, tachyarrhythmia and syncope, and the prevention of sudden cardiac death. Recent years have seen significant developments in our understanding of arrhythmias. Recent technological developments include ever smaller and more complex implantable pacing devices, the ability to map an arrhythmia circuit in three dimensions, potentially in one beat, and the ability safely to damage small areas of myocardium known to be critical to a particular arrhythmia, leading to permanent cure. This article focuses on the diagnostic tools that can be used to investigate these conditions, and its sister article (see 'Supraventricular and ventricular arrhythmias: interventional management' in Medicine 2022; 50 (8)) deals with some of the treatment strategies.